2018
DOI: 10.1007/s10646-018-1895-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of two fungicides on enchytraeid and earthworm communities under field conditions

Abstract: Because of the wide use of pesticides in agriculture, there is still a need of higher-tier field studies to assess ecotoxicological effects of commercial formulations on a wider variety of non-target soil organisms such as soil annelids. We here tested the effects of different concentrations of two fungicide formulations, i.e., Cuprafor Micro (composed of 500 g kg copper oxychloride) and Swing Gold (composed of 50 g l epoxiconazole and 133 g l dimoxystrobin) on two families of terrestrial oligochaetes (Lumbric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Cuprafor Micro® made of copper oxychloride and used in organic farming; Swing® Gold made of dimoxystrobin (DMX) and epoxiconazole (EPX), and used in conventional farming) on earthworm communities under field conditions over two years. This study is the continuation of a previous study conducted by Amossé et al (2018). They showed that Swing® Gold at 10 × the recommended field rate (RR) drastically reduced anecic and epigeic earthworm diversity and abundances one month after application.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…Cuprafor Micro® made of copper oxychloride and used in organic farming; Swing® Gold made of dimoxystrobin (DMX) and epoxiconazole (EPX), and used in conventional farming) on earthworm communities under field conditions over two years. This study is the continuation of a previous study conducted by Amossé et al (2018). They showed that Swing® Gold at 10 × the recommended field rate (RR) drastically reduced anecic and epigeic earthworm diversity and abundances one month after application.…”
Section: Introductionsupporting
confidence: 71%
“…These significant effects found at short term (i.e. one month after application) in Amossé et al (2018) persisted for at least twelve months after the fungicide application.…”
Section: Impacts Of the Tested Fungicides On Earthworm Communities Over Two Yearsmentioning
confidence: 90%
See 3 more Smart Citations